Progresses in DNI measurements in Southern Portugal - Cavaco, Afonso (2018)
The present work describes the progresses made in the measurement of Direct Normal Irradiance (DNI) in the south of Portugal (Southern Europe), with a network of eleven solar radiation measurement stations in several locations scattered through this region. Since the beginning of this initiative, in 2014, the network has increased from 8 to 11 measuring stations and will, in a short time, increase to 12. The increase in the number of measuring locations and of the period of measurements leads to a better characterization of the region in terms of DNI availability and creates conditions for in depth studies. This kind of infrastructure is essential for the region, which is known for its high annual availability of Global Horizontal Irradiance (GHI) and its reduced inter-annual variability, thus a high DNI annual availability is also expected together with a low inter-annual variability. This effort aims at highlighting the potential of Southern Portugal as a prime location for the development and implementation of Concentrated Solar Power (CSP) Plants. A preliminary map of DNI availability is presented, with estimated values ranging from 1841 to 2073 kWh/m2/year. These results were compared with the DNI availability estimated from 13 years (2003-2015) of global and diffuse irradiance measurements in one of the locations of the network (Évora, central Alentejo), and a good agreement was found, thus providing some statistical value to the recent DNI measurements.